2004
DOI: 10.1093/jxb/erh134
|View full text |Cite
|
Sign up to set email alerts
|

Activity and protein level of AO isoforms in pea plants (Pisum sativum L.) during vegetative development and in response to stress conditions

Abstract: Among three AO isoforms detected in pea plants, the activity of PAO-1 was dominant in leaves of seedlings and young leaves of mature plants, while PAO-3 revealed the highest band intensity in old leaves and roots. PAO-1 and PAO-3 are homodimers consisting of 145 kDa and 140 kDa subunits, respectively, while PAO-2 is a heterodimer of one 145 kDa and one 140 kDa subunit. In leaves, the activity of PAO-1 disappeared gradually with leaf ageing, while in roots it was present only in seedlings but not in mature pea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 43 publications
4
27
0
Order By: Relevance
“…A barley (Hordeum vulgare) AO present in leaves, roots, and seeds was capable of oxidizing a number of aliphatic and aromatic aldehydes (Omarov et al, 1999). Additionally, pea (Pisum sativum) leaves possessed AO activity with indole-3-acetaldehyde and abscisic aldehyde (Zdunek-Zastocka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A barley (Hordeum vulgare) AO present in leaves, roots, and seeds was capable of oxidizing a number of aliphatic and aromatic aldehydes (Omarov et al, 1999). Additionally, pea (Pisum sativum) leaves possessed AO activity with indole-3-acetaldehyde and abscisic aldehyde (Zdunek-Zastocka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The final step of ABA biosynthesis is catalyzed by ABA aldehyde oxidase, which requires molybdenum cofactor. 30) It has been reported that Ntdin functions in molybdenum cofactor biosynthesis 31) and hence, these clones might be involved in ABA biosynthesis. Expression of selected genes during manufacture Expression of up-regulated genes during the manufacturing process was evaluated by RT-PCR.…”
Section: Identification Of Up-regulated Transcriptsmentioning
confidence: 99%
“…Plant AO belongs to a multigene family (Ando et al 2006;Min et al 2000;Ori et al 1997;Sekimoto et al 1997Sekimoto et al , 1998Zdunek-Zastocka 2008), whose members differ in electrophoretic mobility and subunit composition (Akaba et al 1999;Seo et al 2000b;Koiwai et al 2000;Omarov et al 2003;Zdunek-Zastocka et al 2004) and exhibit broad substrate specificity (Koiwai et al 2000;Akaba et al 1998). Plant AO has only been purified from coleoptiles of maize (Koshiba et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Four cDNAs of AO genes from Arabidopsis (Sekimoto et al 1998), three putative AO genes and two AO pseudogenes from tomato (Min et al 2000;Ori et al 1997), three cDNAs from pea (Zdunek-Zastocka 2008), and one AhAO1 cDNA from peanut ) have been reported. However, isoforms that can efficiently oxidize ABAld to ABA have only been identified in Arabidopsis rosette leaves (AOδ; Seo et al 2000b), barley roots (AO2 and AO3; Omarov et al 2003), and pea roots and leaves (PAO2 and PAO3; Zdunek-Zastocka et al 2004). Among the AO genes, the expression of AAO3, TAO1, and TAO3 was increased rapidly in response to drought stress (Seo et al 2000b;Yesbergenova et al 2005).…”
Section: Introductionmentioning
confidence: 99%